Consolidating the Weimar Triangle: European policy functions of German-Polish-French co-operation - Kai-Olaf Lang; Daniela Schwarzer (Stiftung Wissenschaft und Politik (SWP), 2011)
Twenty years have passed since the launch of the Weimar Triangle. Yet apart from anumber of glitzy summits, the German, Polish and French co-operation can hardly beconsidered as having played an influential role in European politics. Nonetheless,trilateral collaboration could certainly take on a number of useful functions in the EU,providing the community with urgently needed capacities such as leadership, consensusbuilding or strategic guidance. In times of crises and turmoil it is certainly thepressing challenges of economic and financial policy where joint Weimar initiativescould be profitable for the EU. But the trio could also play its part in European securityand defence policy, one of the few areas, where the Triangle is beginning to produceresults, or neighbourhood and energy policy, where current strategies are in need ofreassessment. If co-operation between Germany, France and Poland is to become moreconsistent, trilateral consultational structures will have to be strengthened
Keywords: 320